Flirting with Danger : Young Women's Reflections on Sexuality and Domination. - Phillips, Lynn (Qualitative studies in psychology., 2000)
In Flirting with Danger, Lynn M. Phillips explores how young women make sense of, resist, and negotiate conflicting cultural messages about sexual agency, responsibility, aggression, and desire. How do women develop their ideas about sex, love, and domination? Why do they express feminist views condemning male violence in the abstract, but often adamantly refuse to name their own violent and exploitive encounters as abuse, rape, or victimization?. Based on in-depth individual and collective interviews with a racially and culturally diverse sample of college-aged women, Flirting with Danger sh.